2012
DOI: 10.3201/eid1811.120629
|View full text |Cite
|
Sign up to set email alerts
|

Community Outbreak of Adenovirus, Taiwan, 2011

Abstract: Adenovirus type 7 caused a high proportion of severe infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
75
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 32 publications
11
75
1
Order By: Relevance
“…A similar study in which high HAdV infections (47.6%) were shown at the age group ≤ 1 to ≥3 years compared to age group 3-≤ 6 years and 6-≤ 15 years at 28.1%, 11%, respectively [35]. The study finding is also, comparable to other studies of HAdV infection in other part of the world indicating that children under the age of 3 years were most susceptible to HAdV infection [36][37][38]. In previous experiments for the detection of HAdV in RTI, we observed that Children at age between 6 to 15 years usually have a lower rate of infection.…”
Section: Molecular Diagnosis Of Human Adenovirus In Children With Uppsupporting
confidence: 80%
“…A similar study in which high HAdV infections (47.6%) were shown at the age group ≤ 1 to ≥3 years compared to age group 3-≤ 6 years and 6-≤ 15 years at 28.1%, 11%, respectively [35]. The study finding is also, comparable to other studies of HAdV infection in other part of the world indicating that children under the age of 3 years were most susceptible to HAdV infection [36][37][38]. In previous experiments for the detection of HAdV in RTI, we observed that Children at age between 6 to 15 years usually have a lower rate of infection.…”
Section: Molecular Diagnosis Of Human Adenovirus In Children With Uppsupporting
confidence: 80%
“…A corresponding rise was noted among military personnel during October 2012-April 2013, but no statistically significant increase in Ad7 infections was detected by the NPHL community ILI surveillance program. Partial hexon gene sequences of the Singapore isolates had 100% nucleotide identity with sequences reported from outbreaks in Taiwan and China (2,3,10).…”
Section: Discussionmentioning
confidence: 92%
“…Recent reports have noted increased incidence of severe Ad7 disease in Asia: among the general population and pediatric inpatients in Taiwan; among persons in a military training camp in Shaanxi, China; and among those in a police training center in Kuala Lumpur, Malaysia (2)(3)(4). During January-June 2013, physicians in Singapore noted an increase in HAdV pediatric inpatients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, control of HAdV7 spread is crucial. However, it is difficult to differentiate pneumonia caused by HAdVs from other types of viral pneumonia, and culturing and typing of HAdVs are not routinely performed in hospitals (18). Therefore, the inevitable delay of several days in the recognition of HAdV infections probably promoted the transmission.…”
mentioning
confidence: 99%